2021
DOI: 10.18781/r.mex.fit.2103-2
|View full text |Cite
|
Sign up to set email alerts
|

Verbesina sphaerocephala extracts promote the development of Cucumis sativus and reduce the damage caused by Meloidogyne incognita

Abstract: Uno de los principales problemas fitosanitarios son los nematodos agalladores del género <em>Meloidogyne</em>. El uso de <em>Verbesina sphaerocephala</em> podrían sustituir el uso de nematicidas químicos. El objetivo de esta investigación fue probar si extractos acuosos de <em>V. sphaerocephala</em> promueven el desarrollo y reducen los daños ocasionados por <em>M. incognita</em> en <em>Cucumis sativus</em>. Se evaluaron siete tratamientos en plantas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The allelopathic response that caused the extracts of V. sphaerocephala and V. fastigiata to inhibit seed germination in the plants in this study points mainly to the quantity and quality of phenolic compounds, as indicated in a phytochemical study carried out on the aqueous extracts of the species V. sphaerocephala, in which the authors emphasize its high content of phenolic compounds [19]. While low concentrations can favor development, high concentrations inhibit the same.…”
Section: Effect Of V Sphaerocephala and V Fastigiata Extracts On The ...mentioning
confidence: 66%
See 3 more Smart Citations
“…The allelopathic response that caused the extracts of V. sphaerocephala and V. fastigiata to inhibit seed germination in the plants in this study points mainly to the quantity and quality of phenolic compounds, as indicated in a phytochemical study carried out on the aqueous extracts of the species V. sphaerocephala, in which the authors emphasize its high content of phenolic compounds [19]. While low concentrations can favor development, high concentrations inhibit the same.…”
Section: Effect Of V Sphaerocephala and V Fastigiata Extracts On The ...mentioning
confidence: 66%
“…We did not detect nitrates and K compounds were not detected in the extracts, which could be due to the fact that the extracts are considered organic, and that these nutrients could be absorbed and assimilated by plants through enzymatic activation derived from various proteins contained within the extract. The species of Verbesina sphaerocephala has a high content of organic matter, carbohydrates, and proteins [19]. However, results may vary according to the phenological state of the leaves used to obtain the extracts and may even vary based on the analytical method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations